Fluid-mineral dynamics at the Rincón de la Vieja volcano—hydrothermal system (Costa Rica) inferred by the study of major, minor and rare earth elements in the hyperacid crater lake - Pappaterra, Sabrina; Inguaggiato, Claudio; Rouwet, Dmitri; Levresse, Gilles; Peiffer, Loic; Apollaro, Carmine; Mora-Amador, Raúl; Ramírez-Umaña, Carlos; González, Gino; Schiavo, Benedetto; Kretzschmar, Thomas Gunter; Brusca, Lorenzo (Frontiers in Earth Science, 2023)
Volcanic lakes are complex natural systems and their chemical composition is related to a myriad of processes. The chemical composition of major, minor, Rare Earth Elements (REE) and physico-chemical parameters at the hyperacid crater lake of Rincón de la Vieja volcano (Costa Rica) are here investigated during February 2013–August 2014. The study of the lake chemical composition allows to identify the main geochemical processes occurring in the lake and to track the changes in the volcanic activity, both important for active volcanoes monitoring. The total REE concentration (∑REE) dissolved in the crater lake varies from 2.7 to 3.6 mg kg−1 during the period of observation. REE in the water lake samples normalized to the average volcanic local rock (REEN-local rock) are depleted in light REE (LREE). On the contrary REEN-local rock in the solids precipitated (mainly gypsum/anhydrite), from lake water samples in laboratory at 22°C, are enriched in LREE. The low variability of (La/Pr)N-local rock and (LREE/HREE)N-local rock ratios (0.92–1.07 and 0.66–0.81, respectively) in crater lake waters is consistent with the low phreatic activity (less than 10 phreatic eruptions in 2 years) observed during the period of observation. This period of low activity precedes the unrest started in 2015, thus, it could be considered as a pre-unrest, characterized by infrequent phreatic eruptions. No clear changes in the REE chemistry are associated with the phreatic eruption occurred at mid-2013. The results obtained investigating water-rock interaction processes at the Rincón de la Vieja crater lake show that rock dissolution and mineral precipitation/dissolution are the main processes that control the variability of cations composition over time. In particular, precipitation and dissolution of gypsum and alunite are responsible for the variations of REE in the waters. Despite the low variations of (La/Pr)N-local rock and (LREE/HREE)N-local rock ratios, this study allows to suggest that REE can be used, together with major elements, as practical tracers of water-rock interaction processes and mineral precipitation/dissolution at active hyperacid crater lakes over time, also during periods of quiescence and low phreatic activity.